Coração, cabeça e estômago: uma narrativa reflexiva sobre a trajetória no curso de medicina na Universidade Federal de São Carlos - Lisboa, Uliana Pereira da Silva (Universidade Federal de São Carlos, 2024)
The critical-reflective narrative format as a final course work is foreseen in the Pedagogical Project of the Medicine Course at UFSCar. Throughout the following pages, I describe part of my journey through medical sciences, which begins in childhood as a vague, playful, and fantastic idea, and gradually gains concreteness and complexity as the years pass and new scenarios emerge, providing intimate accounts and reflections of this entire intense and inexhaustible process of medical training. As an avid and passionate consumer of literature and the humanities in general, I was inspired, with the due adaptations, by the triple division observed in the novel "Head, Heart, and Stomach", by Camilo Castelo Branco. In the first cut, "heart", brings the beginning of the process of building the desire for medicine, still in childhood, a side with a more idealistic and fantastic predominance. Subsequently, in "head", this more fanciful and rudimentary idea begins to gradually take on a more concrete and complex tone, which ranges from the preamble of approval to graduation itself. Finally, in "stomach", there is a closing with a more immediate reflection of what has been nourishing and driving me in the present.
Heart, Head, and Stomach: a reflective narrative on the trajectory in the medical course at the Federal University of São Carlos
Keywords: Narrativa crítica; Formação médica; Identidade profissional; Experiência subjetiva; Humanidades; CIENCIAS DA SAUDE::MEDICINA